The Fractional Transportation Problem with Interval Demand, Supply and Costs - Kocken, Hale Gonce; Emiroglu, Ibrahim; Guler, Coskun; Tasci, Fatih; Sivri, Mustafa (AMER INST PHYSICS, 2013)
The data of real world applications generally cannot be expressed strictly. An efficient way of handling this situation is expressing the data as intervals. Thus this paper focuses on the Interval Fractional Transportation Problem (IFTP) in which all the parameters i.e. cost and preference coefficients of the objective function, supply and demand quantities are expressed as intervals. A Taylor series approach is presented for IFTP by means of the expression of intervals with its left and right limits. Also a numerical example is executed for the linear case to illustrate the procedure.
Keywords: Fractional Transportation Problem; Interval numbers; Taylor Series; Mathematics; Physics